Remembering Mrs. Rossi - Hest, Amy.; Maione, Heather Harms (Cambridge, Mass. : Candlewick Press, 2007)
Although she loves her father, their home in New York City, and third-grade teacher Miss Meadows, Annie misses her mother who died recently.
Accelerated Reader AR
Keywords: Teacher-student relationships -- Juvenile fiction; Grief -- Juvenile fiction; Death -- Juvenile fiction; Parent and child -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction